IEEE Information Theory Workshop 2010 (ITW 2010) 2010
DOI: 10.1109/itwksps.2010.5503154
|View full text |Cite
|
Sign up to set email alerts
|

Testing composite hypotheses about discrete-valued stationary processes

Abstract: Given a discrete-valued sample X1, . . . , Xn we wish to test whether it was generated by a stationary ergodic process belonging to a family H0, or it was generated by a stationary ergodic process outside H0. Apart from the assumptions of stationarity and ergodicity, no further probabilistic or parametric assumptions are made. We require the Type I error of the test to be uniformly bounded, while the probability of Type II error has to tend to zero as the sample size increases. For this notion of consistency w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
4
2

Relationship

6
0

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…testing the hypothesis "k-order Markov process" versus "stationary ergodic, not k-order Markov"), testing for membership to parametric families, and others [12,16,17,21,22]. Some recent general results that characterize those hypotheses about finitely-valued ergodic processes that can be tested are provided in [23]. Finally, a related problem is that of prediction or forecasting [19,14,15,20].…”
Section: Introductionmentioning
confidence: 99%
“…testing the hypothesis "k-order Markov process" versus "stationary ergodic, not k-order Markov"), testing for membership to parametric families, and others [12,16,17,21,22]. Some recent general results that characterize those hypotheses about finitely-valued ergodic processes that can be tested are provided in [23]. Finally, a related problem is that of prediction or forecasting [19,14,15,20].…”
Section: Introductionmentioning
confidence: 99%
“…Prior work. This work continuous our previous research [13,14], which provides similar necessary and sufficient conditions for the existence of a consistent test, for a weaker notion of asymmetric consistency: Type I error is uniformly bounded, while Type II error is required to tend to 0 as the sample size grows.…”
Section: Introductionmentioning
confidence: 56%
“…It is worth noting that the information theory is deeply connected with statistics of time series and signal processing; see, for example, [1,2,5,7,10,11,13,14,15] and [8,9,6], correspondingly. In this paper a new connection of this kind is established: it is shown that the Shannon entropy determines the rate of growth of the size of the confidence set for the signal, given its version corrupted by stationary noise.…”
Section: Introductionmentioning
confidence: 99%